On preparation of Poland's regions to knowledge-based economy - Stanislaw Walukiewicz; Tadeusz Zoltowski; Aneta Kaminska (European Regional Science Association (ERSA), 2002)
Poland is in a phase of preparing intensively to the European Union Membership intensifying negotiation process and making necessary adjustments of its law and structures. One of actions is preparation to attain Poland's readiness to use Structural Funds. Apart of fulfilling legal and institutional accession requirements, Poland must undertake an effort transitioning from middle income economy to the innovation-based economy in order to participate in the European Union policy oriented for enhancing its competitiveness. The objective of this contribution is to analyse the ability of existing regions in Poland (NUTS2) to fulfil requisites to create regions based on knowledge-for-development, such as setting up institutional and economic environment that enables free flow of knowledge, supporting ITC, encouraging innovation and entrepreneurship. Moreover it will be studied to what extent the educated and skilled population in selected regions can create, share and use knowledge. Finally the paper will discuss a situation regarding networks of research institutions, universities, industry (particularly with special concern on SMEs clusters), trying to reveal whether they are ready to use national and international knowledge and creating own knowledge. The above analysis will be presented in the framework of workpackages structure developed in the proposal of the IKINET project.
Keywords: 330